The Digitalization in Insurance Broker Industry: How Artificial Intelligence Affect This Industry - Khalisa, Arvidhia (Ilomata International Journal of Management, 2024)
This qualitative research explores the impact of digitalization, with a particular focus on artificial intelligence (AI), on the insurance broker industry. In-depth interviews and focus group discussions were conducted with eight senior-level employee and eight younger participants from technology and operations departments, also from client-facing positions. The research aimed to analyze the impact of digitalization, especially artificial intelligence, to the insurance broker industry and to explore whether artificial intelligence is capable to replace an insurance broker role. The findings indicate that digitalization, including the adoption of AI, has brought about significant advancements in the industry. Digitalization efforts have led to streamlined processes, reduced costs, improved data analysis, and enhanced customer experiences. The findings of this research highlight the importance of taking a deliberate and strategic approach to digitalization and AI adoption in the insurance broker industry. Companies should use technology to increase efficiency while maintaining the human-centric elements that are essential for developing strong client relationships and providing tailored insurance solutions.